BBC NEBOR MY NEBOR AND RURAL HEALTH COMMUNICATION IN RIVERS STATE - Anyanwu, B.J.C.; Ikpegbu, Emmanuel O.U. (African Journal of Social and Behavioural Sciences, 2022)
It is believed that many Nigerians who live in rural areas suffer from preventable health problems. Communication ought to provide people with instructive health messages, which entertainment education promises. This paper focused on BBC Media Action Nebor My Nebor radio drama series in addressing rural health in River State. The paper had three objectives which were to find out the motivation, satisfaction and influence of the radio drama serial on rural health communication. The study employed the Entertainment Theory with the Uses and Gratifications Theory. We adopted the descriptive survey design with a population of 4, 592, 588, drawn from the rural dwellers in Rivers State. It adopted the cluster and purposive sampling procedures with a sample size of 297, drawn from three communities in each of the Senatorial Zones – Rivers East, Rivers West and Rivers South East. The instrument for data collection was designed to have 11 items of which five were constructed in four-point Likert Scale format. The criterion for decision-making was 2.5.The paper found out that language and presentation styles were the key variables motivating listenership giving the 53% when summed; an understanding of health issues, especially diarrhoea, personal hygiene and ORT gave the audience a sense of satisfaction as well as influenced their attitudes, favourably, giving the Average weighted Mean score (AWMS) of 3.36. The paper then concluded that BBC Nebor My Nebor is meeting its objective of rural health communication and recommended that the use of indigenous languages should be explored for subsequent programmes.